Використання інформаційних технологій в аграрному бізнесі - Мороз, Світлана Іванівна; Moroz, Svitlana; Карамушка, Олександр Миколайович; Karamushka, Oleksandr; Шрамко, Інна Іванівна; Shramko, Inna (Дніпровський державний аграрно-економічний університет, 2018)
Кризові умови господарювання та висока конкуренція у галузі вимагають від аграрних товаровиробників використовувати всі доступні шляхи й резерви для зниження витрат, пошуку постачальників, виробництва та пропонування споживачам якісної продукції. Зазначене можливе лише на основі аналізу великої кількості інформації засобами інформаційних технологій. Технології комп’ютерних мереж є структурною складовою будь-якої сучасної автоматизованої інформаційної системи та необхідним елементом виробничої та комерційної діяльності підприємства. Розробники програмного забезпечення пропонують для автоматизації бізнесових функцій серверні та хмарні рішення. Лідером у розробці та поширенні веб та мобільних додатків є Google. Встановлено, що мережні технології та реалізовані на їх основі ресурси доцільно використовувати в аграрному бізнесі для рішення завдань пошуку інформації, організації електронного документообігу, управління проектами, оптимізації діяльності та прогнозування, маркетингу та збуту, спілкування з фіскальними службами, банкінгу, комунікацій, управління виробничими процесами, навчання персоналу. Crisis conditions and high competition in the industry require agrarian commodity producers to use all ways and means to reduce costs, search for suppliers, production and offer consumers quality products. This is only possible on the basis of analysis of a large amount of information through information technology and the use of modern electronic business. The aim of the article is to study the current state of network technologies and web services and determine the prospects for their use by specialists of agrarian enterprises. Technology of computer networks is a structural component of any information system and an essential element of production and business activity of the enterprise. Software developers offer server and cloud solutions for automating business functions. Google is the leader in developing and distributing web and mobile applications. Favourable factors in the use of network technologies by agrarian producers are: an increase in the level of Internet penetration to 65%, including 56% in rural areas; the distribution of mobile Internet, with the volume of access twice as high as from stationary devices, which allowed to eliminate the problem of complex network access at production areas and remote villages; development of 3G and 4G networks at speeds above leading networks; the price for access services is low compared to the European one. It is established that network technologies and resources based on them should be used in the agrarian business for solving information search tasks, organizing electronic document circulation, project management, optimization of activity and forecasting, marketing and sales, link with State Fiscal Service, banking, communications with partners and clients, management of productions processes, staff training. Network technologies in leading companies are used by all employees, including specialists working with information systems, managers for communication with customers and suppliers and project management, marketers in the processes of promotion and sales of products by e-commerce, employees in working with production process management systems, etc.
Using of information technologies in agrarian business
Keywords: інформаційні системи; information systems; мережі; network; веб-сервіси; web services; мобільні додатки; mobile applications; аграрний бізнес; agribusiness